Handbook for academic authors - Luey, Beth (Cambridge University Press, 2022)
"When our work is accepted, we share our happiness with colleagues. When it is rejected, we keep our disappointment to ourselves. That very natural response unfortunately makes an author receiving that first rejection believe (despite the statistics on acceptance rates) that this has never happened to anyone else. At some point, something you write will be rejected by a journal or book publisher. To lessen the trauma, I'm going to tell you the story of this book - now in its sixth edition, with thousands of copies sold around the world. The story begins with a rejection letter. In 1985 I completed a manuscript that I titled "A Handbook for Academic Authors" and asked a colleague to read it for me. I knew he was an excellent critical reader, though totally tactless. I revised to respond to his many comments and sent the manuscript to University Press A, which I thought was an obvious fit. They rejected it almost immediately, with what I suspect was a form letter. I was irritated, but because it clearly hadn't gone to outside readers I felt the rejection had nothing to do with the quality of my work. The next day I sent query letters and sample chapters to twelve publishers: six university presses, and six commercial publishers of quality nonfiction. Soon two more rejection letters arrived on a single day: a university press editor informed me that it was an excellent idea but more suitable for a trade publisher; a trade editor said it was an excellent idea but belonged at a university press. Two more form rejections followed"--